Observing Debate in Learning on Students’ Critical Thinking - A. Jauhar Fuad; I Wayan Ardhana; Sulton Sulton; Dedi Kuswandi (Pascasarjana UM, 2018)
Abstract: The objective of this research prove of difference between the limited critical thinking ability and the general critical thinking ability of learners using the methods of debate and discussion with learners who have different learning styles. Using a quasi-experimental design with testing and rating scales, the results showed: (1) there is no difference between the limited critical thinking ability of learners between students who use the method of debate and discussion. There is a difference between the general critical thinking ability of learners between students using the method of debate and those who are using discussion method (2) there is a difference in limited critical thinking ability and the general critical thinking ability between converging learning styles and divergent learning styles; (3) there is an interaction between instructional methods and learning styles on the limited critical thinking ability. The effect of learning methods to the general critical thinking ability is not influenced by the style of learning.Key Words: debate methods, discussion methods, learning styles, critical thinkingAbstrak: Tujuan penelitian ini adalah untuk membuktikan perbedaan antara kemampuan berpikir kritis terbatas dan kemampuan berpikir kritis umum peserta didik menggunakan metode debat dan diskusi dengan gaya belajar yang berbeda. Penelitian ini menggunakan desain kuasi-eksperimental dengan skala pengujian dan penilaian. Hasil menunjukkan: (1) tidak ada perbedaan antara kemampuan berpikir kritis terbatas peserta didik di antara siswa yang menggunakan metode debat dan diskusi. Ada perbedaan antara kemampuan berpikir kritis umum peserta didik di antara siswa yang menggunakan metode debat dan diskusi; (2) ada perbedaan dalam kemampuan berpikir kritis terbatas dan kemampuan berpikir kritis umum antara siswa dengan gaya belajar konvergen dan divergen; (3) ada interaksi antara metode pembelajaran dan gaya belajar pada kemampuan berpikir kritis terbatas. Pengaruh metode pembelajaran terhadap kemampuan berpikir kritis umum tidak dipengaruhi oleh gaya belajar.Kata kunci: metode debat, metode diskusi, gaya belajar, berpikir kritis